Clinical Manifestations and Neuroimaging Features of Intracranial Infection among Study at a Tertiary Care Hospital in Bangladesh - Khan, Ashraf Uddin; Sajedeen, Sharmeen; Akhter, Niksar; Moureen, Adneen; Sattar, AFM Arshedi; Hassan, Mohammad Sayeed (Bangladesh Journal of Medical Microbiology, 2025)
Background: Intracranial infection is one of the life-threatening infections that can affect the meninges or the brain. It is a major cause of emergency and death in children and adults. Preconception regarding the clinical manifestation of intracranial infection may be helpful for physicians in managing such emergency cases. Objective: This study was aimed to assess the clinical manifestation and neuro-radiological features among patients presented with intracranial infections. Methodology: This was a cross-sectional observational study that was conducted in the Department of Radiology and Imaging (CT section) of BSMMU and Dhaka Medical College Hospital, Dhaka, Bangladesh from March 2006 to September 2006. In total 50 patients, by using the spiral CT system with various complaints suspecting intracranial infections and few number of pre-diagnose cases for evaluation of complications were enrolled in this study as the study subjects by random sampling technique. Data were processed, analyzed and disseminated by using MS Office. Results: Male patients contributed 66.0% of the total; most of the patients who underwent a CT of the brain were from 31 to 50 years old. As the most frequent complaint, fever, headache and vomiting were observed in 24.0%, 20.0% and 16.0% of the cases; in about half of the patients (46.0%) high-grade fever was found. As the CT finding, abnormal meningeal enhancement (11.5%), cerebral oedema (7.5%) and mild ventricular dilatation with subarachnoid space enlargement (8.5%) were found among a noticeable number of patients. Conclusion: The prevalence of intracranial infection among males is about double that in females. Fever, headache and vomiting are the most common complaints of intracranial infection patients. Abnormal meningeal enhancement, cerebral oedema and mild ventricular dilatation with subarachnoid space enlargement are very common CT findings in such cases. Bangladesh Journal of Medical Microbiology, July 2024;18(2):75-79